Toxicity of individual naphthenic acids to Vibrio fischeri - Jones, D.; Scarlett, Alan; West, C.; Rowland, S. (2011)
Numerous studies have suggested that the toxicity of organic compounds containing at least one carboxylic acid group and broadly classified as "naphthenic acids", is of environmental concern. For example, the acute toxicity of the more than 1 billion m3 of oil sands process-affected water and the hormonal activity of some offshore produced waters has been attributed to the acids. However, experimental evidence for the toxicity of the individual acids causing these effects has not been very forthcoming. Instead, most data have been gathered from assays of incompletely characterized extracts of the water, which may contain other toxic constituents. An alternative approach is to assay the individual identified toxicants. Since numerous petroleum-derived naphthenic acids and some in oil sands process water, have recently been identified, we were able to measure the toxicity of some individual acids to the bioluminescent bacterium, Vibrio fischeri. Thirty-five pure individual acids were either synthesized or purchased for this purpose. We also used the US EPA ECOSAR computer model to predict the toxicity of each acid to the water flea, Daphnia magna. Both are well-accepted toxicological screening end points. The results show how toxic some of the naphthenic acids really are (e.g., V. fischeri Effective Concentrations for 50% response (EC50) 0.004 to 0.7 mM) and reveal the influence of hydrophobicity and aqueous solubility on the toxicities. Comparison with measured toxicities of other known, but more minor, constituents of oil sands process water, such as polycyclic aromatic hydrocarbons and alkylphenols, helps place these toxicities into a wider context. Given the reported toxicological effects of naphthenic acids to other organisms (e.g., fish, plants), the toxicities of the acids to further end points should now be determined. © 2011 American Chemical Society.